2020
DOI: 10.14569/ijacsa.2020.0110862
|View full text |Cite
|
Sign up to set email alerts
|

Study on Dominant Factor for Academic Performance Prediction using Feature Selection Methods

Abstract: All educational institutions always try to investigate the learning behaviors of students and give early prediction toward student's outcomes for interventing and improving their learning performance. Educational data mining (EDM) offers various effective prediction models to predict student performance. Simultaneously, feature selection (FS) is a method of EDM that is utilized to determine the dominant factors that are needed and sufficient for the target concept. FS method extracts high-quality data that red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…Comparing the results with the research carried out by [31] where a lower accuracy value of 80% was obtained in the predictive system for the training data and 76% for the validity data, this study presents higher performance results. In turn, in the investigation of [27], 82.87% accuracy was obtained using the decision tree algorithm, representing a lower value than the result of our investigation.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Comparing the results with the research carried out by [31] where a lower accuracy value of 80% was obtained in the predictive system for the training data and 76% for the validity data, this study presents higher performance results. In turn, in the investigation of [27], 82.87% accuracy was obtained using the decision tree algorithm, representing a lower value than the result of our investigation.…”
Section: Discussioncontrasting
confidence: 75%
“…Within the two supervised learning techniques, is the classification, the classification algorithms look for patterns that will then allow them to classify the elements and determine which groups or classes they belong to. It should be mentioned that the values for these algorithms must be discrete values [27]. Among the classification algorithms is Kernel, which extends the regular logistic regression, used for binary classification, to deal with data that are not linearly separable [28].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the term optimal model, in [4] it is pointed out that the so-called optimal models are combined with the dominant sets, which significantly improve the performance of prediction models and are highly influential in academic performance factors. Likewise, regarding the area on the curve, whose highest value in this research was 0.93 or 93%, in [4] it is indicated that an AUC of 50% of 91% or 99%, which was obtained in the research represents a better Classifier algorithm performance, favorable results for research.…”
Section: Discussionmentioning
confidence: 99%
“…The information and communication technology (ICT) sector is currently a leader in the analysis of data from different media [1], [2], such as virtual platforms, survey administration software, among other technological tools [3], [4], which capture or acquire information to be processed and analyzed in descriptive statistical research or in research on predictive models applicable to various areas of knowledge [5].…”
Section: Introductionmentioning
confidence: 99%
“…The proposed algorithm could illustrate high performance compared with previous methods that were used before considering the same datasets. In [ 24 ], two feature selection methods are combined (CHI and MI) to measure the performance, which could evaluate the scores of features. The new features' scores had been normalized then, measuring the performance of the student in the education process as it considered important agent from the multiagent that were found in the educational sector.…”
Section: Related Workmentioning
confidence: 99%